Accountability of Shell Company's Practices in Tax Law Perspective by Limited Liability Companies: A Review of Good Corporate Governance - Jessica Ariana Hutagaol; M. Rizki Yudha Prawira (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The use of shell companies by limited liability companies as a means of tax avoidance demonstrates a legal abuse that impacts the dilemma of legal compliance and business ethics. This action raises questions regarding the implementation of good corporate governance, which should be the basic ethics of every company. This study used a normative juridical method through a statutory approach and a conceptual approach. This study utilizes primary, secondary, and tertiary legal materials and then examines them descriptively. The results of the study indicate that the use of shell companies for tax avoidance purposes is contrary to the principles of good corporate governance. This scheme in practice can be subject to tax and criminal sanctions in its accountability.